Destruction and Construction: Application of Dearomatization Strategy in Aromatic Carbon–Nitrogen Bond Functionalization. (9th November 2015) - Wang, Shuo‐En; Wang, Linfei; He, Qiuqin; Fan, Renhua
Abstract: The formation of carbon–carbon bonds through the functionalization of aromatic carbon–nitrogen bonds is a highly attractive synthetic strategy in the synthesis of aromatic molecules. In this paper, we report a novel aromatic carbon–nitrogen bond functionalization reaction by using a simple dearomatization strategy. Through this process para ‐substituted anilines serve as a potential aryl source in the construction of a range of functionalized aromatic molecules, such as quaternary carbon centers, α‐keto esters, and aldehydes.